2020
DOI: 10.1101/2020.04.25.20079095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pooled RNA sample reverse transcriptase real time PCR assay for SARS CoV-2 infection: a reliable, faster and economical method

Abstract: 22 Background 23 Corona virus disease 2019 (COVID-19) which initially started as a cluster of pneumonia 24 cases in the Wuhan city of China has now become a full blown pandemic. Timely diagnosis 25 of COVID-19 is the key in containing the pandemic and breaking the chain of transmission. 26 In low and middle income countries availability of testing kits has become the major bottle 27 neck in testing. Novel methods like pooling of samples are the need of the hour. 28 Method 29 Extracted RNA samples were randomly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…11 Another three studies performed group testing by taking relatively small pool sizes of 5 to 10 samples. [12][13][14] Abdalhamid et al observed that positive samples (detected by individual testing) remain positive even if pooled with 4 negative samples. They created 21 pools with each pool containing 5 samples (1 known positive + 4 known negative).…”
Section: Optimal Pool Sizementioning
confidence: 99%
See 2 more Smart Citations
“…11 Another three studies performed group testing by taking relatively small pool sizes of 5 to 10 samples. [12][13][14] Abdalhamid et al observed that positive samples (detected by individual testing) remain positive even if pooled with 4 negative samples. They created 21 pools with each pool containing 5 samples (1 known positive + 4 known negative).…”
Section: Optimal Pool Sizementioning
confidence: 99%
“…Thirty four pools out of 35, showed concordance with individual testing, that is, 95.4% pools correctly identified the positive samples. 14 Two simulation studies parameterized various pool sizes and multistage testing schemes and compared their efficiency at different prevalence rates. 15, 16 Eberhardt et al found that three-stage schemes performed optimally for prevalence rates up to 12%, and that initial pool sizes of 16 samples were best for prevalence rates up to 3.5% and pools of 9 samples for rates between 3.5% and 12% (P9S3, improvement factor 3.8 to 1.5).…”
Section: Optimal Pool Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The pooling method was validated for nCov tests by many laboratories [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, the following questions remained open, which we address in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…This compromise in cycles was present in both probe-and dye-based assays. However, an increase of CT values from 33,1 to 35,6 cycles (2.5 cycles) has been shown between individual analysis and pool test with 8 samples (1/7 positive), respectively (Gupta et al, 2020). Similarly, another study showed that a positive sample of SARS-CoV-2 can be detected using TaqMan assays in pooled samples without compromising the assay sensitivity (Ben-Ami et al, 2020).…”
Section: Pooling Testmentioning
confidence: 98%